Filossilicatos sintéticos como cargas minerais para obtenção de nanocompósitos base poliuretano - Prado, Manoela Argenton (2018)
The research on polymeric nanocomposites aims to obtain new materials with different properties when compared to the already existing. In this context, this research field are constantly growing. Lamellar phyllosilicates like talcs have been applied as reinforcement for polymeric nanocomposites preparation and achieved significant improvements in these matrices. Polyurethanes are polymers used as matrix for nanocomposites preparation. This work presents the comparation of nanocomposites prepared with solvent based polyurethane and aqueous based polyurethane by the physical mixing method, using as filler new synthetic Ni-talcs with different Ni ratios (ST25Ni, ST50Ni, ST75Ni and ST100Ni) as powder and in gel form. Experiments have also been made with magnesium-based synthetic talc with wine natural dyes adsorbed on these Mg nanotalcs. The talcs were incorporated in relation to the weight of the solvent based polyurethane (3 wt.%) and aqueous based polyurethane (WPU) (1 wt.% to 10 wt.%). In samples produced with solvent based polyurethane Ni-talc (powder) was well incorporated into the polymeric matrix in an intercalated form. These nanocomposites presented low thermal stability when compared to the pure matrix and good results in tension and deformation tests due to the talc/PU interaction by hydrogen bonds. Nanocomposites produced with Ni-talc (gel) were synthesized with ST25Ni, ST50Ni, ST75Ni and ST100Ni as filler. Filler dispersion occurred in an intercalated and exfoliated way with better thermal and mechanical stability for ST25Ni and ST50Ni. Results evidenced that the Ni amount in the filler has an influence in thermal and mechanic properties of the produced nanocomposites. The addition of talc/dye to the polymeric matrix showed that at 10% talc the thermal resistance is improved. These new materials that complement the functionalized polymers market.